The philosophy of David Kaplan - Almog, Joseph; Leonardi, Paolo (Oxford : Oxford University Press, 2009)
Kaplan's intellectual influence on 20th century analytic philosophy has been transformative. This volume collects new previously unpublished articles on Kaplan, analysing many topics, from cutting edge linguistics and the philosophy of mathematics, to metaphysics, the foundations of pragmatics, and the theory of communication.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Kaplan, David -- 1933-; Philosophy, American -- 20th century